Real-world data on adult AML with FLT3-ITD mutation from the Thai acute leukemia working group - Rattanathammethee, Thanawat; Rattarittamrong, Ekarat; Wanitpongpun, Chinadol; Kungwankiattichai, Smith; Owattanapanich, Weerapat; Chanswangphuwana, Chantiya; Polprasert, Chantana; Piyajaroenkij, Thanakrit; Niparuck, Pimjai; Saengboon, Supawee; Limvorapitak, Wasithep; Silpsamrit, Panachai; et al. (Frontiers in Oncology, 2025)
BackgroundFLT3-ITD mutations are among the most common genetic alterations in acute myeloid leukemia (AML) and are associated with poor clinical outcomes. However, data from low- and middle-income countries remain limited. This study aimed to investigate the prevalence, clinical characteristics, treatment patterns, and outcomes of adult AML patients with FLT3-ITD mutations in Thailand.MethodsWe analyzed data from 360 adult patients with newly diagnosed AML, prospectively collected from 11 institutions nationwide between 2016 and 2023. FLT3-ITD mutational status, clinical features, response to therapy, and survival outcomes were compared between FLT3-ITD and FLT3-wild-type patients.ResultsFLT3-ITD mutations were detected in 28.1% of patients. FLT3-ITD patients had higher white blood cell counts, bone marrow blast percentages, and NPM1 co-mutations compared to wild-type FLT3. Induction chemotherapy rates were similar, but FLT3 inhibitor use was nearly absent. Complete remission was achieved in 55.7% of FLT3-ITD patients versus 66.5% in wild-type FLT3. Median overall survival was significantly shorter in the FLT3-ITD group (8.8 vs. 13.2 months, p=0.039), while relapse-free survival was not significantly different. Multivariable analysis confirmed FLT3-ITD mutation as an independent predictor of poor overall survival.ConclusionsIn this nationwide real-world study, FLT3-ITD AML was associated with inferior outcomes despite comparable induction therapy. Limited access to FLT3-targeted treatments and stem cell transplantation may contribute to these disparities. Our findings highlight the urgent need for expanding access to molecular testing and targeted therapies in resource-limited settings.